2013
DOI: 10.1177/0951484813512287
|View full text |Cite
|
Sign up to set email alerts
|

What causes international variations in length of stay: A comparative analysis for two inpatient conditions in Japanese and Canadian hospitals

Abstract: Hospital average length of stay varies considerably between countries. However, there is limited patient-level research identifying or discounting possible reasons for these differences. This study compares the length of stay of patients in Japan, where it is the longest in the OECD, and Canada, where length of stay is closer to the OECD mean. Administrative patient-level data, including age, gender, co-morbidities, intervention, discharge plan, outcome and length of stay were collected from two Japanese and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…As shown in Figures 2 and 3, the mean length of stay only decreased in the Ewha Womans University Medical Center after clinical pathway implementation, whereas that of Gachon University Gil Medical Center showed no significant changes. 34 Therefore, generalizability may be limited, as there are differences with healthcare systems and cultural norms between countries. As clinical pathways are designed to standardize clinical processes and minimize variations, their effectiveness can be measured by the rate of change in SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figures 2 and 3, the mean length of stay only decreased in the Ewha Womans University Medical Center after clinical pathway implementation, whereas that of Gachon University Gil Medical Center showed no significant changes. 34 Therefore, generalizability may be limited, as there are differences with healthcare systems and cultural norms between countries. As clinical pathways are designed to standardize clinical processes and minimize variations, their effectiveness can be measured by the rate of change in SD.…”
Section: Discussionmentioning
confidence: 99%
“…33 Many factors, including professional or cultural norms, difference of payment schemes, and access to long-term care facilities, may contribute to the international differences in length of stay. 34 Therefore, generalizability may be limited, as there are differences with healthcare systems and cultural norms between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the greater relative availability of hospitals and hospital beds in some jurisdictions over others suggests highly variable hospital utilization. For instance, Japan's much more accessible hospitals and hospital beds, both in terms of hospital/citizen and bed/citizen ratios as well as spatial considerations, helps explain their 16.5 day average hospital stay, the longest average hospital stay of all OECD countries [4,17].…”
Section: Discussionmentioning
confidence: 99%
“…Provided health services consist of hospital beds, method of payment and hospital discharge policy; demand for health services include severity of disease, direct and indirect cost of patients, and patient comorbid diseases (9). Tiessen conducted a study in two countries of Japan and Canada, which evaluated factors affecting LOS showed that different factors, including age, gender, type of intervention, type of disease, and many clinical and nonclinical factors, even culture, cause huge difference in LOS between these two countries (10). The result of Yin study indicated that a significant relation existed between level of hospital financial support dependent on patient activity and LOS in elderly people suffering from ischemic heart disease (11).…”
Section: Introductionmentioning
confidence: 99%